2011
DOI: 10.1177/1474651411413192
|View full text |Cite
|
Sign up to set email alerts
|

Hypertriglyceridaemia, LPL deficiency and pancreatitis -pathogenesis and therapeutic options

Abstract: Severe hypertriglyceridaemia (HTG) is recognised as the third most common cause of acute pancreatitis. While secondary causes of HTG such as excess alcohol, obesity and diabetes are well recognised, identification and treatment of primary genetic disorders such as lipoprotein lipase (LPL) deficiency remain a challenge. HTG secondary to such genetic disorders does not respond to established medical therapy, resulting in recurrent episodes of acute pancreatitis. A very low fat diet remains first-line therapy in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The disease is characterized by hyperchylomicronaemia and severe hypertriglyceridaemia, which in turn, are associated with an increased risk of clinical complications, including diabetes mellitus [1][2][3][4]. However, the most debilitating clinical manifestation of the disease is recurrent, severe and potentially life-threatening acute pancreatitis, with severe hypertriglyceridaemia being one of the primary risk factors for pancreatitis and the third leading cause of acute pancreatitis [2][3][4]. Pancreatitis is associated with an increased risk of pancreatic cancer [5] and results in significant morbidity and mortality in 20-30 % of patients, impacting on health-related qualityof-life and placing a significant economic burden on healthcare systems [3,4].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The disease is characterized by hyperchylomicronaemia and severe hypertriglyceridaemia, which in turn, are associated with an increased risk of clinical complications, including diabetes mellitus [1][2][3][4]. However, the most debilitating clinical manifestation of the disease is recurrent, severe and potentially life-threatening acute pancreatitis, with severe hypertriglyceridaemia being one of the primary risk factors for pancreatitis and the third leading cause of acute pancreatitis [2][3][4]. Pancreatitis is associated with an increased risk of pancreatic cancer [5] and results in significant morbidity and mortality in 20-30 % of patients, impacting on health-related qualityof-life and placing a significant economic burden on healthcare systems [3,4].…”
mentioning
confidence: 99%
“…The disease is characterized by hyperchylomicronaemia and severe hypertriglyceridaemia, which in turn, are associated with an increased risk of clinical complications, including diabetes mellitus [1][2][3][4]. However, the most debilitating clinical manifestation of the disease is recurrent, severe and potentially life-threatening acute pancreatitis, with severe hypertriglyceridaemia being one of the primary risk factors for pancreatitis and the third leading cause of acute pancreatitis [2][3][4].…”
mentioning
confidence: 99%
“…The precise mechanism of pancreatitis due to SHTG is not known. It has been suggested that high local levels of FFA released by pancreatic lipase during hydrolysis of TG present in chylomicrons exceed the binding capacity of albumin and induce inflammation [11,12]. According to another hypothesis, increased chylomicron levels lead to excessive plasma viscosity, resulting in hypoxia and local acidosis in pancreatic capillaries, which increases toxicity of FFA [13].…”
Section: Pancreatitismentioning
confidence: 99%